PENGARUH MODEL ADVANCE ORGANIZER DENGAN PETA KONSEP UNTUK MENINGKATKAN KEMAMPUAN STRATEGIC COMPETENCE MATEMATIS SISWA SMP - Mellawaty (Universitas Wiralodra, 2016)
Strategic mathematical competence is one focus of mathematical proficiency. But  in  reality  they  encountered  students who   are   low   mathematical   ability   of strategic competence. One alternative learning that can improve students  strategic competence mathematical is a model Advance Organizer   with a concept map. This study aims to determine the increase in strategic      mathematical competence capability of students who received Organizer Advance model learning with concept maps and students who obtain teaching  expository  method.  This  study used an experimental method. The population in this study were students of class VII SMP Negeri 1 Kroya Indramayu and taken two classes at random according to the class as a sample. Instruments used in this research is test the ability of strategic mathematical competence. Based on the analysis  of  research  data,  we  concluded that, by enhancing the strategic competence of  students  who  obtain  a  mathematical model study Advance Organizer to map the concept better than students who received learning expository method.